2011
DOI: 10.1111/j.1541-0420.2011.01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Inference for Causal Interactions for Continuous Exposures under Dichotomization

Abstract: Summary Dichotomization of continuous exposure variables is a common practice in medical and epidemiologic research. The practice has been cautioned against on the grounds of efficiency and bias. Here we consider the consequences of dichotomization of a continuous covariate for the study of interactions. We show that when a continuous exposure has been dichotomized certain inferences concerning causal interactions can be drawn with regard to the original continuous exposure scale. Within the context of interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Although this group includes drinkers, no excess risk was found among men consuming 1–5 drinks per day when compared with never drinkers. We nevertheless conducted sensitivity analyses using different dichotomisation points, which led to similar conclusions; our findings are, therefore, not likely to be due to erroneous modelling of the exposure variables 32. In addition, although misclassification cannot be totally ruled out, as previously discussed, it has been shown that when investigating additive interaction, the probability of misclassification should be substantial (at least larger than ¼) to bias the results 33.…”
Section: Discussionsupporting
confidence: 73%
“…Although this group includes drinkers, no excess risk was found among men consuming 1–5 drinks per day when compared with never drinkers. We nevertheless conducted sensitivity analyses using different dichotomisation points, which led to similar conclusions; our findings are, therefore, not likely to be due to erroneous modelling of the exposure variables 32. In addition, although misclassification cannot be totally ruled out, as previously discussed, it has been shown that when investigating additive interaction, the probability of misclassification should be substantial (at least larger than ¼) to bias the results 33.…”
Section: Discussionsupporting
confidence: 73%
“…Second, measurement error and misclassification of both spot urine BPA concentrations and self-reported folate intake are possible, and this would likely attenuate associations [71]. However, tests for interaction, using the misclassified exposures, are valid provided the probability of misclassification satisfies certain bounds [72]. Measured exposures have correlation close to 0 and misclassification of them is likely independent, therefore, in similar scenarios [72], evidence for significant interaction remains.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Certain publications, focusing on dichotomous risk factors, have explored additive interaction through rothman's indexes. [2][3][4][5][6][7] Continuous risk factors have been investigated for specific cases only 8 (eAppendix 1; http://links.lww.com/eDe/ A771). We consider here the setting of continuous risk factors X, Y for disease D (0 = absence, 1 = presence), such as the probability that D = 1 increases with higher values of X, Y.…”
Section: Lettersmentioning
confidence: 99%
“…In these data, the outcome was rare (<10%), and so the above indexes are applicable. 5 the association of hypertension with BMI and nonadherence to a Mediterranean diet, estimated through logistic regression, with and without their interaction term, is shown in the table and etable 2 (http://links.lww.com/eDe/ A771), respectively. In etable 2, both factors are shown to be positively associated with prevalence of hypertension (Or BMI = 1.14 and Or NMD = 1.18, respectively).…”
Section: Lettersmentioning
confidence: 99%